MV X선의 방사선 선량 증강 현상에서 물리적 특성과 이차입자의 발생 - 황철환; Chulhwan Hwang; 김정훈; Junghoon Kim (한국방사선학회 논문지, 2019)
선량 증강 현상에서 발생하는 물리적 특성과 증강 물질과의 상호 작용으로부터 발생하는 이차입자 생성을 평가하였다. Geant4, MIRD 두부 팬텀을 이용한 몬테카를로 전산 모사를 진행하였으며, 선형가속기에서 발생되는 4, 6, 10, 15, 18, 25 MV X선을 선원으로 적용하였다. 10, 20, 30 mg/g의 금(aurum), 가돌리늄(gadolinium) 증강 물질을 팬텀 내부 종양에 모사하였으며, 물리적 상호작용의 변화와 이차입자 발생에 따른 입자 플루언스와 초기 에너지로부터 방사선가중인자를 고려하여 등가선량을 평가하였다. 방사선 선량 증강 물질에 의한 상호작용은 고 원자번호에서 기인하여 광전효과에 의한 에너지 흡수를 높이는 것으로 나타났으며, 10 MV 이상의 에너지에서는 광핵반응의 증가를 나타내었다. 이로 인해, 팬텀 내부에서 양성자, 중성자와 같은 이차입자 발생의 증가를 보였으며, 중성자에 의한 등가선량이 최대 424.2배 증가하는 것으로 나타났다. 본 연구는 선량 증강 현상에서의 에너지 전달, 흡수의 물리적 과정을 모사하여, 증강 현상에서 발생하는 물리적 특성을 분석하고자 하였다. 이러한 결과는 향후 in-vivo, in-vitro 선량 증강 실험을 위한 기초 자료로 활용될 수 있을 것으로 사료된다. We evaluated the physical properties that occur to dose enhancement and changes from secondary particle production resulting from the interaction between enhancement material. Geant4 was used to perform a Monte Carlo simulation, and the medical internal radiation dose (MIRD) head phantom were employed. X-rays of 4, 6, 10, 15, 18, and 25 MV were used. Aurum (Au) and gadolinium (Gd) were applied within the tumor volume at 10, 20, and 30 mg/g, and an experiment using soft tissue exclusively was concomitantly performed for comparison. Also, particle fluence and initial kinetic energy of secondary particle of interaction were measured to calculate equivalent doses using the radiation weight factor. The properties of physical interaction by the radiation enhancement material showed the great increased in photoelectric effect as compared to the compton scattering and pair production, occurred with the highest, in aurum and gadolinium it is shown in common. The photonuclear effect frequency increased as the energy increased, thereby increasing secondary particle production, including alpha particles, protons, and neutrons. During dose enhancement using aurum, a maximum 424.25-fold increase in the equivalent dose due to neutrons was observed. This study was Monte Carlo simulation corresponds to the physical process of energy transmission in dose enhancement. Its results may be used as a basis for future in vivo and in vitro experiments aiming to improve effects of dose enhancement.